ANALISIS PENERAPAN MERIT SYSTEM OLEH BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA (BKPSDM) DALAM PENEMPATAN PEGAWAI DI SEKRETARIAT DAERAH KABUPATEN LINGGA TAHUN 2020 - Khairil Chandra; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Promotion and transfer of employees at the Regional Secretariat of Lingga Regency by the Personnel and Human Resources Development Agency of Lingga Regency resulted in the placement of employees who were not based on the suitability between employee qualifications and the qualifications for position requirements as well as the existence of a political element in the promotion and transfer process. This study aims to determine the application of the merit system in Promotions and Transfers at the Regional Secretariat of Lingga Regency in 2020 and the factors that influence it. Qualitative research. This, using Kartono's theory (2001: 210) that there are 5 aspects that become the parameters of the implementation of the merit system, namely: Education and Training; Experience; Skills; Ethics; and Working Time. The results of the research show that the implementation of the merit system in implementing employee transfers at the Regional Secretariat in 2020 was not fully implemented. Most of the aspects that become indicators are not implemented at all. The application of the merit system is influenced by 3 factors, namely, the limited human resources factor, the two legal factors that have loopholes and the disobedience of the organizers and the subjectivity factor, the interests of certain parties. Keywords: Education and Training, Experience, Skills, Ethics, and Years of Service